9(x+8)=4(2x+18)+x

Simple and best practice solution for 9(x+8)=4(2x+18)+x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(x+8)=4(2x+18)+x equation:


Simplifying
9(x + 8) = 4(2x + 18) + x

Reorder the terms:
9(8 + x) = 4(2x + 18) + x
(8 * 9 + x * 9) = 4(2x + 18) + x
(72 + 9x) = 4(2x + 18) + x

Reorder the terms:
72 + 9x = 4(18 + 2x) + x
72 + 9x = (18 * 4 + 2x * 4) + x
72 + 9x = (72 + 8x) + x

Combine like terms: 8x + x = 9x
72 + 9x = 72 + 9x

Add '-72' to each side of the equation.
72 + -72 + 9x = 72 + -72 + 9x

Combine like terms: 72 + -72 = 0
0 + 9x = 72 + -72 + 9x
9x = 72 + -72 + 9x

Combine like terms: 72 + -72 = 0
9x = 0 + 9x
9x = 9x

Add '-9x' to each side of the equation.
9x + -9x = 9x + -9x

Combine like terms: 9x + -9x = 0
0 = 9x + -9x

Combine like terms: 9x + -9x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| y^3+2y^2=2y+50 | | -11.2+4(2.1+q)=-.8 | | x-8.4=-5.2 | | N+5=21 | | 3[3(b-5)+17]-[3(3b-2)+5]= | | 2t+8=-5 | | 56.25=.50(x+4)(2) | | 5x-12=7x+4 | | X+9=-(2x+2) | | 33-6x=-24 | | 2x^3-72x= | | 3+4(3n+6)-n= | | p^2-6p+5=0 | | [9(b+4)-15]-[3(b-4)+3]= | | bc=3x+2 | | .05x+13=9 | | 5r-2r+3=7r-r | | 7x^2-7x-84= | | -2y=10x+16 | | (3x+5)(x+3)=7 | | 6x-y+5=180 | | 7x-248+x+44=180 | | 30-4x=14 | | 5(x-7)=2(2-2x)-3 | | [9(x+5)-16]+[3(x-2)+4]= | | x+8-1/3=90/11 | | 2x^2+8x-192=0 | | 3x+(x*x)=180 | | 0.06(10-x)(100)= | | x^2-5x=x(5+x) | | x^2-5x=x(5x) | | 2x+55=272 |

Equations solver categories